Common Concerns of Cancer Patients in the Time of COVID-19 Outbreak: Some Implications for Health Care Professionals - Zohreh Shahhosseini; Fatemeh Hamidi (Shahrekord University of Medical Sciences, 2021)
Dear Editor, Coronaviruses are important human and animal pathogens. In December 2019, a new virus from the coronavirus family, called coronavirus disease 2019 (COVID-19), triggered the outbreak of pneumonia from Wuhan across China. The virus originated in bats and was transmitted to humans through unknown intermediate animals. Currently, the lives of millions of people around the world are affected by the crisis caused by the outbreak of COVID-19 diseases, which has brought huge economic and social costs. Despite the efforts made in many countries to reduce the risks and the negative effects of this crisis, the damage and the resulting costs are still increasing. People with cancer are among the groups that need more attention and are highlighted as high-risk groups. The risk of morbidity and mortality from COVID-19 as a consequence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is not uniform. Evidence show that patients with cancer have an increased risk of developing severe forms of COVID-19 compared with the non-cancer population. It seems that cancer patients are at a higher risk of respiratory viruses such as influenza because of their frequently observed immunocompromised state. Patients with blood malignancies, such as non-Hodgkin lymphoma, chronic lymphocytic leukemia, acute myeloid leukemia, acute lymphoblastic leukemia, and multiple myeloma, along with those in active treatment for any type of cancer and people who have undergone bone marrow transplants are among the high-risk groups.   According to the existing literature on COVID-19 pathogenesis and cancer, several shared features have been selected to define the risk assessment in cancer patients, including patient characteristics (such as older age, underlying diseases, obesity, and sex), disease characteristics, therapeutic characteristics, and clinical and laboratory variables. Given the competitive risks of cancer-related deaths and serious complications from SARS-CoV-2 and higher mortality, providing care for cancer patients in this crisis is a challenging task. Many cancer patients are seeking to find a cure for their disease due to cancellation or delay in treatment, including surgery, chemotherapy, and radiation therapy. There are also concerns that patients with curable cancers, who need timely treatments, find the risk of COVID-19 higher than the benefits of cancer treatment. New findings from researchers in the United States show that 13% of patients, including cancer patients, who used a combination of azithromycin and hydroxychloroquine or just hydroxychloroquine for treatment died within one month. However, further testing is needed to determine the risks and benefits of these drugs. It has recently been reported that using a combination of the two drugs to treat cancer patients infected with COVID-19 has tripled their risk of death within 30 days. Hence, it is recommended that these patients do not use the mentioned drugs. Insufficient provision of personal protective equipment for health care providers, limited hospital capacity, including intensive care units, may be effective in providing care to people with cancer. Early treatment of cancer patients should not be compromised during the pandemic. However, patient management should be tailored to the best available resources, and the need for any intervention should be balanced against the increased risk of pandemic. In addition, alternative modified procedures, including counseling and treatment services such as home care and tele-nursing should be considered for cancer patients. The goals, alternative modified procedures, including counseling and treatment services, were to ensure the continuity of care and to protect the health care professionals from the infection. Health scholars in different disciplines have proposed another method to manage cancer patients; according to these scholars, in special circumstances, cyberspace like "WhatsApp", "Telegram", or "Instagram" should be used to communicate with patients and share educational materials and information. Moreover, training nurses to respond appropriately to patient needs, such as stress management and proper nutrition, is essential. Outpatients should be treated with the safest level of care and away from any danger. Several measures may help reduce the virus transmission as follows: training the proper communication rules and hand hygiene protocols, explaining infection control measures, teaching the signs and symptoms of COVID-19, highlighting the importance of staying home and non-exposure to high-risk individuals, and emphasizing the importance of reporting any new symptoms to physicians and health care providers. Attendance at the clinic should be limited only to patients themselves and a maximum of one companion; in addition, outpatient care clinics, including chemotherapy injection units should have careful screening and be prepared to identify possible cases safely and without risk of transmission. Currently and due to the limited data, there are no international guidelines to address the management of cancer patients in any infectious pandemic, but for each patient, a separate decision should be made according to age, general condition, stage, and spread of the disease, and the patients should consult their physician about this issue. At present, more than ever, the world needs to espouse perspectives free of race, religion, ethnicity, and gender to help countries come together for the sake of the health of all populations. Community participation, attention to the health of all cancer patients in all age groups, non-discrimination, access to quality services and information, and appropriate collaboration can help in this regard.